2012
DOI: 10.1002/erv.2157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Attitudes towards Change and Self‐directness on Dropout in Eating Disorders: A 2‐Year Follow‐up Study

Abstract: The clinician's challenge is to help eating disorders patients to develop an unyielding sense of responsibility and self-acceptance, aimed to integrate the therapeutic choice into their own intrapersonal frame of goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…The positive impact of treatment on motivation to change appears to have a long term effect, with nine of the 11 studies that included a follow‐up measure of motivation finding that improvements were maintained, or continued to increase, across all time points up to 2 years (Dean et al, ; Geller et al, ; Leung, Ma, & Russell, ; Leung, Ma, & Russell, ; Rodríguez‐Cano & Beato‐Fernández, ; Rodríguez‐Cano et al, ; Touyz et al, ; Wade, Treasure & Schmidt, , Pellizzer, unpublished). Only one study, Ackard et al (), found that motivation to change dropped below baseline over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive impact of treatment on motivation to change appears to have a long term effect, with nine of the 11 studies that included a follow‐up measure of motivation finding that improvements were maintained, or continued to increase, across all time points up to 2 years (Dean et al, ; Geller et al, ; Leung, Ma, & Russell, ; Leung, Ma, & Russell, ; Rodríguez‐Cano & Beato‐Fernández, ; Rodríguez‐Cano et al, ; Touyz et al, ; Wade, Treasure & Schmidt, , Pellizzer, unpublished). Only one study, Ackard et al (), found that motivation to change dropped below baseline over time.…”
Section: Resultsmentioning
confidence: 99%
“…Potential differences in the effect of interventions on motivation to change between different eating disorder diagnoses is difficult to ascertain as only two studies provided sub‐group analysis for motivational changes based on eating disorder type (Allen et al, ; Rodríguez‐Cano et al, ). However in both cases, while significant changes in motivation to change were found for all participants, the pattern of change was different between sub‐groups.…”
Section: Resultsmentioning
confidence: 99%
“…Impairment in positive aspects, often neglected in research, is noteworthy as there is evidence that such deficits may be associated with chronicity or relapse in EDs (Espindola & Blay, 2009;Rodríguez-Cano, Beato-Fernandez, Moreno, & Vaz Leal, 2012) and in other psychiatric populations (Fava, 2012;Ryff, 2014). Moreover, the lack of differences in a couple of studies on self-liking and social functioning between remitted or recovered patients and healthy controls may warrant larger studies to support such findings.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consensual definition of remission creates difficulties when comparing outcome data from treatment modalities and centers, so we emphasize the need for uniform adoption of remission definitions. 28 Furthermore, the high incidence of dropout as in the case of the majority of literature, 24,33 as well as in our study, largely decreases the power and generalization of the results.…”
Section: Resultsmentioning
confidence: 49%
“…23 Data from standard clinical practice reveal that dropout rates have not changed over the course of time, regardless of country or treatment modality, reaching 50% or more for both outpatient and inpatient samples. 24,25 In our program we had 55% dropout rate, 11.2% of which matching early dropouts, a favorable value compared to previous estimates among outpatient eating disorder services of 13 -32%. 26 We do not know exactly the major reasons for premature treatment termination of our patients but resistance to treatment and reluctance to recovery have been long recognized as key-problems in the treatment, as well as illness duration, treatment type and family variables.…”
mentioning
confidence: 83%